Answer:
This is easy -- it's just a list of steps. At this level, the problems are pretty simple.
Let's just do one, then I'll write out the list of steps for you.
Find the inverse of f( x ) = -( 1 / 3 )x + 1
STEP 1: Stick a "y" in for the "f(x)" guy:
y = -( 1 / 3 )x + 1
STEP 2: Switch the x and y
( because every (x, y) has a (y, x) partner! ):
x = -( 1 / 3 )y + 1
STEP 3: Solve for y:
x = -( 1 / 3 )y + 1 ... multiply by 3 to ditch the fraction ... 3x = -y + 3 ... ditch the +3 ... subtract 3 from both sides ... 3x - 3 = -y ... multiply by -1 ... -3x + 3 = y ... y = -3x + 3
STEP 4: Stick in the inverse notation, f^( -1 )( x )
f^( -1 )( x ) = -3x + 3
Step-by-step explanation:
Answer:
26/33
Step-by-step explanation:
The process is:
0.787878
78.7878
78/99x then simplify
Answer:
<em>120°, 120°, 60°, 60°</em>
Step-by-step explanation:
m∠1 = 180° - 60° = 120°
m∠1 = m ∠2 (alternate interior)
m∠3 = 60° (vertical to given angle)
m∠4 = m∠3 (alternate exterior)